20.4k views
4 votes
Find the indicated values, where g(t) = t^2 - t and f(x) = 1 + x g(f(3)-2f(1))

Find the indicated values, where g(t) = t^2 - t and f(x) = 1 + x g(f(3)-2f(1))-example-1
User Installero
by
5.3k points

1 Answer

5 votes

Answer:

B. 0

Explanation:

Given

g(t) = t² - t

f(x) = 1 + x

Required

Find g(f(3) - 2f(1))

First, we'll solve for f(3)

Given that f(x) = 1 + x

f(3) = 1 + 3

f(3) = 4

Then, we'll solve for 2f(1)

2f(1) = 2 * f(1)

2f(1) = 2 * (1 + 1)

2f(1) = 2 * 2

2f(1) = 4

Substitute the values of f(3) and 2f(1) in g(f(3) - 2f(1))

g(f(3) - 2f(1)) = g(4 - 4)

g(f(3) - 2f(1)) = g(0)

Now, we'll solve for g(0)

Given that g(t) = t² - t

g(0) = 0² - 0

g(0) = 0 - 0

g(0) = 0

Hence, g(f(3) - 2f(1)) = 0

From the list of given options, the correct answer is B. 0

User Maul
by
5.7k points